Teacher Power and the Politics of Union Organizing in the Charter Sector. Issue 1 (January 2020) - Jabbar, Huriya; Chanin, Jesse; Haynes, Jamie; Slaughter, Sara
Despite the growing media attention paid to charter-school unions, comparatively little empirical research exists. Drawing on interview data from two cities (Detroit, MI, and New Orleans, LA), our exploratory study examined charter-school teachers' motivations for organizing, the political and power dimensions, and the framing of unions by both teachers and administrations. We found that improving teacher retention, and thus school stability, was a central motivation for teacher organizers, whereas, simultaneously, high teacher turnover stymied union drives. We also found that charter administrators reacted with severity to nascent unionization drives, harnessing school-as-family metaphors and at-will contracts to prevent union formation. As the charter sector continues to grow, understanding why teachers want unions and how those unions differ from traditional public school unions is crucial to analyzing the long-term viability of these schools and the career trajectories of the teachers who work in them.